Biodiversity and Evaluation of Genetic Resources of Some Coffee Trees Grown in Al-Baha, Saudi Arabia - Fatima Omari Alzahrani; Mohammed Obeid Alshaharni; Gamal Awad El-Shaboury; Abdelfattah Badr (Current Issues in Molecular Biology)
The biodiversity of 12 coffee (Coffea arabica L.) cultivars collected from the Al-Baha region in the southwest of Saudi Arabia was evaluated using 25 morphological variations and genetic diversity as demonstrated by molecular polymorphism generated by eight Inter Simple Sequence Repeats (ISSRs) and nine Start Codon Targeted (SCoT) primers. Substantial variations were scored in the morphological traits reflected in the clustering of the examined cultivars in PCA of the coffee cultivars. The examined cultivars were grouped in two groups, one included the cultivars coded Y5, Y6, R113, and Y7 and the other group comprised two clusters; one comprised cultivars coded R8 and R4 and the other comprised cultivars R112, R114, and Y2. In the meantime, the cultivars coded R9 and R111 were differentiated together from other cultivars, while the Y3 cultivar was confirmed by the analysis of ISSR data and SCoT data, which also support the grouping of R9 and R111 cultivars. Principle Component Analysis (PCA) of morphological, ISSR, and SCoT data as a combined set differentiated the examined species into four groups in a scatter plot in agreement with their separation in the cluster trees. The diversity profile among the examined C. arabica cultivars proved that R111 and R4 cultivars are highly diverse, while R8 and Y5 cultivars exhibit low diversity. Alpha diversity indices indicated that R9 and R111 cultivars are the most dominant and stable C. arabica cultivars among the examined samples in the study region.